2004
DOI: 10.1111/j.1365-2850.2004.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Advancing self‐determination with young adults who have schizophrenia

Abstract: The research examined how community mental health nurses promote self-determination with clients who are experiencing an early episode of schizophrenia. The study used grounded theory methodology incorporating interviews and observations. The study took place in the community, in rural and regional New South Wales, Australia, and involved clients and community mental health nurses. The findings show that the promotion of self-determination is dependent on nurses educating clients about their illness and well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…The findings are in accordance with earlier research regarding person-centred psychoeducational health promotion approaches, which have showed positive changes in thoughts, feelings, and behaviour among participants (Arneson & Ekberg, 2005;Byrne et al, 1999;Mc-Cann & Clark, 2004;Medin et al, 2003;Webster & Austin, 1999). Taking part in decision-making processes is an aspect of person-centred health education, which has shown positive impact on self-determination, self-confidence, capability to reflect on old habits in new ways, and psychosocial functioning (Byrne et al, 1999;McCann & Clark, 2004). Arneson and Ekberg (2005) and Buchanan (2006) found that social support and supporting group contexts are essential for achievement of personal goals.…”
Section: Towards Personal Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings are in accordance with earlier research regarding person-centred psychoeducational health promotion approaches, which have showed positive changes in thoughts, feelings, and behaviour among participants (Arneson & Ekberg, 2005;Byrne et al, 1999;Mc-Cann & Clark, 2004;Medin et al, 2003;Webster & Austin, 1999). Taking part in decision-making processes is an aspect of person-centred health education, which has shown positive impact on self-determination, self-confidence, capability to reflect on old habits in new ways, and psychosocial functioning (Byrne et al, 1999;McCann & Clark, 2004). Arneson and Ekberg (2005) and Buchanan (2006) found that social support and supporting group contexts are essential for achievement of personal goals.…”
Section: Towards Personal Growthsupporting
confidence: 92%
“…Social support and supporting group contexts have been described as essential for transforming personal strategies into action and achieving personal goals (Arneson & Ekberg, 2005;Buchanan, 2006). Research has been carried out on person-centered health education for persons with various forms of vulnerability (Arneson & Ekberg 2005;Byrne et al, 1999;McCann & Clark, 2004;Medin, Bendtsen, & Ekberg, 2003). However research about person-centered health education among people with persistent mental illness is rare.…”
mentioning
confidence: 98%
“…Further, patients highlighted the need for informational support, and having knowledgeable HCPs who can provide guidance on appropriate physical activity. The value of groups, group processes, and the benefit of self-initiated physical activity was congruent with the principles of autonomy, belonging and competence identified by self-determination theory (Deci and Ryan, 2000;Sheldon et al, 1996); the relevance of this theory for understanding the experiences and motives of individuals with schizophrenia has been previously acknowledged (McCann and Clark, 2004). HCPs could use these principles to facilitate physical activity participation.…”
Section: The Vulnerability Of Individuals With Schizophrenia To the Ementioning
confidence: 89%
“…Goal-setting is recognized as having an important role in rehabilitation (Levack et al 2006), but sole reliance on this intervention depicts the nurse-client relationship as low in consultation and high in compliance-seeking (Godin 2000), a benevolent role of choosing patient goals and inducing structure (Lutzén & Nordin 1993). This is not consistent with the collaborative engagement sought by people with enduring mental health problems (O'Brien 2001, McCann & Clark 2004, Adam et al 2003.…”
Section: Classification Of Psychosocial Interventionsmentioning
confidence: 89%